Molecular assessment of complex microbial communities degrading long chain fatty acids in methanogenic bioreactors - Sousa, D. Z. (2007)
Microbial diversity of anaerobic sludge after extended contact with long chain fatty acids (LCFA) was studied using molecular approaches. Samples containing high amounts of accumulated LCFA were obtained after continuous loading of two bioreactors with oleate or with palmitate. These sludge samples were then incubated in batch assays to allow degradation of the biomass-associated LCFA. In addition, sludge used as inoculum for the reactors was also characterized. Predominant phylotypes of the different samples were monitored using denaturing gradient gel electrophoresis (DGGE) of PCR-amplified 16S rRNA gene fragments. Fingerprinting analysis showed changes in bacterial and archaeal communities during LCFA accumulation and degradation. Full-length 16S rRNA gene sequences of 22 clones, representing the predominant bacteria and archaea, were determined. Most bacterial clones (80%) clustered within the Clostridiaceae. Two major groups of methanogens were identified: hydrogen- and formate-utilizing organisms, closely related to Methanobacterium, and acetoclastic organisms closely related to Methanosaeta and Methanosarcina. Quantification by FISH and real-time PCR showed that the relative abundance of archaea increased during degradation of biomass-accumulated LCFA. These results provide insight into the importance and dynamics of balanced communities of bacteria and methanogens in LCFAaccumulation/ degradation cycles.